A preparation method of hydrophobic polyurethane urea binder for road use based on double hydrophobic modification

By using the dual hydrophobic modification method of nanosilica and hydroxypolydimethylsiloxane in the polyurethane urea cement, the problems of easy hydrolysis of polyurethane cement and limited ice and snow removal functions in winter are solved, and efficient hydrophobic performance improvement and durability extension are achieved.

CN118530425BActive Publication Date: 2025-03-14LANZHOU JIAOTONG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410683304.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-29
Publication Date
2025-03-14
Estimated Expiration
2044-05-29

AI Technical Summary

Technical Problem

Polyurethane cement is easy to hydrolyze, resulting in loosening and shedding of polyurethane mixtures during long-term service, reducing their water stability and durability. At the same time, the function of removing ice and snow in winter is limited, and the existing hydrophobic modification methods only achieve physical modification and have limited wear resistance.

Method used

Using the dual hydrophobic modification method, the hydrophobic properties are improved by adding nanosilica and hydroxypolydimethylsiloxane to the polyurethane urea cement.

Benefits of technology

It significantly improves the hydrophobic properties of polyurethane urea cement, extends the service life of polyurethane pavement, enhances its ice and snow removal ability in cold areas, and ensures bonding strength and wear resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118530425B_ABST
    Figure CN118530425B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a road-use hydrophobic polyurethane urea binder based on double hydrophobic modification, and relates to the technical field of polyurethane pavement materials. The invention uses polyurethane, polyurea, hydroxy polydimethylsiloxane, nano silicon dioxide, chain extender and organic solvent as raw materials to prepare a polyurethane urea binder having excellent hydrophobicity, mechanical properties, interface bonding properties, hydrolysis resistance and wear resistance. The material is used as a binder for polyurethane mixture for pavement, which can improve the hydrophobicity of polyurethane pavement, overcome the problem of poor hydrolysis resistance of existing polyurethane binders, and ensure the excellent use performance of polyurethane pavement.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyurethane pavement materials, and in particular to a method for preparing a road-use hydrophobic polyurethane urea binder based on double hydrophobic modification. Background Art

[0002] Polyurethane pavement has received increasing attention in recent years. Compared with traditional asphalt mixtures, polyurethane mixtures can be mixed at room temperature, so they can significantly reduce carbon emissions caused by asphalt heating and are environmentally friendly.

[0003] During the service life of polyurethane pavement, the flame retardancy and low surface temperature of the pavement are beneficial to road traffic safety and the reduction of urban heat island effect. In addition, polyurethane binder has certain elasticity and damping properties. The porous polyurethane mixture prepared by it can be used for self-stressed deicing and snow removal in winter, and can reduce tire-road noise to a certain extent, which has a wide range of application scenarios. Therefore, polyurethane mixtures are currently widely studied in the fields of bridge deck paving, noise reduction pavement and self-stressed deicing and snow removal pavement.

[0004] Although polyurethane mixtures have broad application prospects, the polyurethane binder that plays a bonding role still has the following problems:

[0005] (1) Polyurethane binder is essentially a relatively hydrophilic polymer material. Once water enters the road during its long-term service, long-term water erosion will gradually degrade the polyurethane binder, causing the polyurethane mixture to become loose and fall off, resulting in poor water stability and durability of the polyurethane mixture.

[0006] (2) In terms of active snow and ice removal in winter, although polyurethane elastic pavement relies on its own elasticity to physically remove snow and ice, the effect of this method is limited. Therefore, by modifying the polyurethane binder to make it hydrophobic and combining it with self-stress snow and ice removal, the application environment and application effect of polyurethane elastic pavement for snow and ice removal can be expanded.

[0007] (3) At present, the method for hydrophobic modification of polyurethane binders is mainly to spray nanomaterials on the surface of the binder to create a rough surface to achieve hydrophobic modification. In essence, it is just a simple physical modification method, and the wear resistance achieved is limited.

[0008] Therefore, providing a road polyurethane binder with excellent comprehensive performance to meet the performance requirements of polyurethane pavement is an urgent problem to be solved in the current field. Summary of the invention

[0009] The purpose of the present invention is to provide a method for preparing a road-use hydrophobic polyurethane urea binder based on double hydrophobic modification, so as to solve the problems existing in the above-mentioned prior art and thus meet the performance requirements of polyurethane pavement.

[0010] To achieve the above object, the present invention provides the following solutions:

[0011] One of the technical solutions of the present invention is to provide a polyurethane urea binder, comprising the following raw material components in parts by weight:

[0012]

[0013]

[0014] Wherein, the polyurethane component A is a polyurethane having an NCO / OH molar ratio of 1.5-2.5 and a free NCO mass percentage content of 1%-4%;

[0015] The polyurethane B component is obtained by mixing polyether diol or polyoxypropylene diol and 1,4-butanediol in a mass ratio of 2:1;

[0016] The polyurea A component is a polyurea having a NOC mass fraction between 12% and 15%;

[0017] The polyurea R component is an amino-terminated polyether.

[0018] The second technical solution of the present invention is to provide a method for preparing the above-mentioned polyurethane urea binder, comprising the following steps:

[0019] The raw materials are mixed according to the mass ratio to obtain the polyurethane urea binder.

[0020] The third technical solution of the present invention is to provide the application of the above-mentioned polyurethane urea binder as a binder material in a polyurethane mixture for pavement.

[0021] A fourth technical solution of the present invention is to provide a polyurethane mixture containing the above-mentioned polyurethane urea binder.

[0022] As a further preferred embodiment of the present invention, the mass content of the polyurethane urea binder in the polyurethane aggregate is 4%-7%.

[0023] The fifth technical solution of the present invention is to provide the application of the above-mentioned polyurethane mixture as a pavement material.

[0024] In the present invention, the polyurethane contains a strong polar urethane group. By adjusting the ratio of NCO / OH in the formula, different products of thermosetting polyurethane and thermoplastic polyurethane can be prepared. According to its molecular structure, it can be divided into two types: linear and bulk. Due to different crosslinking densities in the bulk structure, it can present hard, soft or properties between the two, and has the characteristics of high strength, high wear resistance and solvent resistance. The polyurethane component A adopts an existing polyurethane material with an NCO / OH molar ratio of 1.5-2.5 and a free NCO mass percentage of 1%-4%, because thermoplastic bulk polyurethane can be prepared within this molar ratio and percentage range.

[0025] Furthermore, the polyurethane component A used may be a prepolymer obtained by combining polyether diol or polyoxypropylene diol with an excess of 4,4′-diphenylmethane diisocyanate (MDI).

[0026] In the present invention, the polyurethane component B is made of existing polyurethane materials. Further, it can be made by mixing polyether diol and 1,4-butanediol in a mass ratio of 2:1 or by mixing polyoxypropylene diol and 1,4-butanediol in a mass ratio of 2:1.

[0027] In the present invention, in order to control the crosslinking density and reaction rate of the polyurea, the polyurea A component uses an existing polyurea material with a NOC mass fraction of 12% to 15%. Furthermore, a prepolymer obtained by amino-terminated polyether and excess isophorone diisocyanate (IPDI) can be used.

[0028] In the present invention, the polyurea R component is an amino-terminated polyether with a molecular weight of 1000-2000 g / mol.

[0029] The hydroxy polydimethylsiloxane (HPDMS) used in the present invention is a hydroxyl-terminated dimethyl silicone oil. The isocyanate group (-NCO) in the polyurethane urea segment reacts with the hydroxyl group (-OH) of OH-HPDMS to generate a carbamate bond (-NH-CO-O-). Through the above reaction, OH-HPDMS is successfully grafted onto the main chain of the polyurethane urea to form a siloxane-modified polyurethane urea. The purpose of using the hydroxyl-terminated structure is to control the position of the chemical reaction by hydroxyl-terminated, thereby allowing dimethylsiloxane to be grafted onto a specific position of the polyurethane urea binder without affecting other positions. The end-capping reaction can be used to selectively protect the target position, thereby organizing the reaction at other positions.

[0030] As a further preferred embodiment of the present invention, the nano silicon dioxide SiO 2 -The average particle size of NPs is 20nm-35nm.

[0031] As a further preferred embodiment of the present invention, the chain extender is a diamine small molecule chain extender with a molecular weight range of 60-200 g / mol.

[0032] As further preferred embodiment of the present invention, the organic solvent is ethyl acetate or butyl acetate.

[0033] The preferred polyurethane urea binder preparation process of the present invention is as follows:

[0034] (1) mixing the polyurethane component A and the polyurethane component B, and reacting them at 25-40° C. for 45 min-60 min;

[0035] (2) Adding polyurea A component and polyurea R component to the mixture obtained in step (1), and then adding hydroxy polydimethylsiloxane (HPDMS), nano silicon dioxide (SiO 2 -NPs), a chain extender and an organic solvent, and stirring at 25-40° C. to make the materials uniformly stirred to obtain the polyurethane urea binder.

[0036] The present invention provides a road polyurethane urea binder based on a dual combination of physical modification for making a rough surface and chemical modification for low surface energy. 2 The particles are easy to agglomerate to form submicron-scale aggregates, forming raspberry-like particles with a micron-nano binary rough structure, which are used to prepare super hydrophobic surfaces; hydroxy polydimethylsiloxane (HPDMS) is mainly obtained by grafting organic hydrophobic groups in HPDMS into polyurethane urea to reduce the surface energy of the binder, thereby improving its hydrophobic properties. The dual hydrophobic modification method of the present invention, which includes physical modification for making rough surfaces and chemical modification for low surface energy, can greatly improve the hydrophobic properties of polyurethane urea binders, and have good mechanical properties and interface bonding properties.

[0037] The present invention discloses the following technical effects:

[0038] The double hydrophobic modified road hydrophobic polyurethane urea binder of the present invention can well overcome the pavement damage caused by the easy hydrolysis of the polyurethane binder during the service of the polyurethane pavement, thereby extending the service life of the polyurethane pavement.

[0039] The invention performs double hydrophobic modification on the road polyurethane binder so as to avoid the accumulation of water on the surface of the polyurethane pavement and prolong the freezing time of supercooled water, which is beneficial to the use of the polyurethane pavement in icy road sections in cold regions.

[0040] The present invention ensures the bonding strength of the polyurethane binder while performing hydrophobic modification on the polyurethane binder, and adopts a physical and chemical dual modification method different from the existing hydrophobic coating modification, thereby improving the hydrophobic durability of the polyurethane urea binder. It has broad application prospects in polyurethane road materials and ensures the performance of polyurethane road materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0042] Figure 1 The tensile strength curves of the hydrophobic polyurethane urea binder for roads of Examples 1-9 of the present invention;

[0043] Figure 2 The figures show the delayed freezing conditions of the mixtures prepared with hydrophobic polyurethane urea binder in Example 1, Example 5, Comparative Example 1 and Comparative Example 2 in an environment of -20°C. DETAILED DESCRIPTION

[0044] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0045] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0046] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0047] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0048] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0049] The polyurethane component A and the polyurethane component B used in the embodiment of the present invention are polyurethane material A and material B provided by Shandong Jining Juyue New Materials Co., Ltd., model H2151S; the polyurea component A and the polyurea R component used are polyurea material A and material R provided by Hebei Longxiang Insulation Technology Co., Ltd., model ALLGLL-1308; the hydroxy polydimethylsiloxane (HPDMS) used is Dow Corning 184HPDMS; the nano silicon dioxide (SiO 2 -NPs) were 99.5% 30±5nm nano-silica provided by Shanghai MacLean Reagent Co., Ltd.

[0050] Among them: in the above-mentioned H2151S polyurethane A material and B material: the NCO / OH molar ratio of A material is 2.0, and the mass percentage of free NCO is 2.5%; B material is obtained by mixing polyether diol and 1,4-butanediol in a mass ratio of 2:1; the NOC mass fraction of polyurea A material is 14%; the polyurea R component is terminal amino polyether with a molecular weight of 1500g / mol; the molecular weight of the diamine small molecule chain extender is 116g / mol.

[0051] Example 1

[0052] A hydrophobic polyurethane urea binder for road use, the raw materials have the following mass proportions:

[0053]

[0054] The preparation method is as follows:

[0055] First, mix the polyurethane component A and the polyurethane component B, set the reaction temperature to 25°C, the stirring speed to 600r / min, and stir for 3 minutes; then add the polyurea component A and the polyurea R component and stir; then add hydroxyl polydimethylsiloxane, nano-silica, diamine small molecule chain extender and ethyl acetate in sequence, and continue stirring at 25°C for 3 minutes until the binder is evenly stirred. After stirring evenly, place the sample in a 25°C insulation box for 60 minutes to obtain a road hydrophobic polyurethane urea binder.

[0056] Example 2

[0057] A hydrophobic polyurethane urea binder for road use, the raw materials have the following mass proportions:

[0058]

[0059]

[0060] The preparation method is the same as Example 1.

[0061] Example 3

[0062] A hydrophobic polyurethane urea binder for road use, the raw materials have the following mass proportions:

[0063] The preparation method is the same as Example 1.

[0064] Example 4

[0065] A hydrophobic polyurethane urea binder for road use, the raw materials have the following mass proportions:

[0066] The preparation method is the same as Example 1.

[0067] Example 5

[0068] A hydrophobic polyurethane urea binder for road use, the raw materials have the following mass proportions:

[0069]

[0070]

[0071] The preparation method is the same as Example 1.

[0072] Example 6

[0073] A hydrophobic polyurethane urea binder for road use, the raw materials have the following mass proportions:

[0074] The preparation method is the same as Example 1.

[0075] Example 7

[0076] A hydrophobic polyurethane urea binder for road use, the raw materials have the following mass proportions:

[0077] The preparation method is the same as Example 1.

[0078] Example 8

[0079] A hydrophobic polyurethane urea binder for road use, the raw materials have the following mass proportions:

[0080]

[0081]

[0082] The preparation method is the same as Example 1.

[0083] Example 9

[0084] A hydrophobic polyurethane urea binder for road use, the raw materials have the following mass proportions:

[0085]

[0086] The preparation method is the same as Example 1.

[0087] Comparative Example 1

[0088] The only difference from Example 1 is that the raw material components do not contain polyurea A component, polyurea R component, hydroxy polydimethylsiloxane and nano silicon dioxide. The mass fractions of the remaining raw material components and the material preparation method are the same as those in Example 1.

[0089] Comparative Example 2

[0090] The only difference from Example 1 is that the raw material components do not contain hydroxy polydimethylsiloxane and nano silicon dioxide. The mass fractions of the remaining raw material components and the material preparation method are the same as in Example 1.

[0091] Comparative Example 3

[0092] The only difference from Example 1 is that the raw material does not contain nano silicon dioxide and the amount of hydroxy polydimethylsiloxane is 12 parts. The mass fractions of the remaining raw material components and the material preparation method are the same as in Example 1.

[0093] Comparative Example 4

[0094] The only difference from Example 1 is that the raw material does not contain hydroxy polydimethylsiloxane and the amount of nano silicon dioxide is 12 parts. The mass fractions of the remaining raw material components and the material preparation method are the same as those in Example 1.

[0095] The binders prepared in Examples 1-9 and Comparative Examples 1-4 were cast into predetermined sizes, and after being completely cured at room temperature, samples were prepared for testing of hydrophobicity, mechanical properties, interface bonding properties, hydrolysis resistance and wear resistance.

[0096] The test index of hydrophobic performance is: water drop contact angle; the test index of mechanical performance is: tensile strength and elongation at break; the test index of interface adhesion performance is: interface shear strength and interface pull-out strength; the test index of hydrolysis resistance performance is: tensile strength and elongation at break after immersion test; the test index of wear resistance performance is: surface water drop contact angle after abrasion test.

[0097] The performance test results are shown in Table 1-5.

[0098] Table 1 Hydrophobic performance test results

[0099]

[0100] Table 2 Mechanical properties test results

[0101]

[0102] Table 3 Interface bonding strength test results

[0103]

[0104] Table 4 Hydrolysis resistance test results

[0105]

[0106] Table 5 Wear resistance test results

[0107]

[0108] According to Table 1, when polyurea A component, R component, hydroxy polydimethylsiloxane and nano-silica were not added, the obtained polyurethane binder showed hydrophilicity with a contact angle of 75.6°; after adding only polyurea A and polyurea R components, the polyurethane binder showed hydrophobicity; after adding hydroxy polydimethylsiloxane and nano-silica, the contact angle of the material gradually increased, and the nano-silica (SiO 2 -NPs) contribute more to the increase of the contact angle of polyurethane urea binder.

[0109] According to Table 2 and Figure 1 It can be seen that the mechanical properties of the polyurethane urea binder after adding polyurea A and polyurea R components are significantly improved compared with that of comparative example 1, and the tensile strength increases by 28.8%. Then, after adding hydroxyl polydimethylsiloxane and nano-silica, its mechanical properties decrease. Among them, with the increase of nano-silica dosage, the mechanical properties of the polyurethane urea binder decrease more obviously, indicating that the dosage of nano-silica should be strictly controlled.

[0110] According to Table 3, after adding polyurea A and R components, the interfacial bonding strength of the polyurethane urea binder is significantly increased compared with that of Comparative Example 1, wherein the interfacial shear strength increases by 35.6% and the interfacial pull strength increases by 28.8%. Then, with the addition of hydroxy polydimethylsiloxane and nano-silicon dioxide, the interfacial bonding strength decreases slightly, but the effect of nano-silicon dioxide on the interfacial bonding strength of the polyurethane urea binder is more significant.

[0111] According to Table 4, the mechanical properties of the hydrophobic polyurethane urea binder slightly decayed after the immersion test, but the degree of decay was significantly reduced compared with that of the ordinary polyurethane binder. This shows that the addition of polyurea, hydroxy polydimethylsiloxane and nano-silica effectively improved the hydrolysis resistance of the hydrophobic polyurethane urea binder.

[0112] According to Table 5, the contact angles of the hydrophobic polyurethane urea binders all decayed after the abrasion test. With the increase of the nano-silica dosage, the contact angle decayed more. This is mainly because nano-silica mainly performs hydrophobic modification of the polyurethane urea binder by physically creating a rough interface on the surface. Compared with the chemical modification method of adding polyurea and hydroxypolydimethylsiloxane, its durability and wear resistance are insufficient.

[0113] Figure 2 The freezing test diagram of polyurethane urea mixture specimens prepared by binders of Example 1, Example 5, Comparative Example 1 and Comparative Example 2 with the same gradation and a binder-cement ratio of 5%. The polyurethane urea mixture specimens were placed in an environmental box at -20°C for freezing test.

[0114] from Figure 2 It can be seen that after 1 hour in the low temperature environment box, thin ice began to exist on the edge and part of the central area of ​​Comparative Example 1, thin ice began to exist on the edge of Comparative Example 2, and the surface water of Example 1 and Example 5 was still liquid and not frozen. After 3 hours, it can be clearly seen that the de-icing performance of different comparative examples and examples is that most of the surface water of Comparative Example 1 has frozen, and only a small part of liquid water exists in the middle, and the liquid water on the surface of Example 5 has just begun to freeze, which shows that the polyurethane mixture prepared by using hydrophobically modified polyurethane urea binder can significantly delay the freezing time of supercooled water on the road surface.

[0115] Application Example 1

[0116] The polyurethane urea binder prepared in Example 5 was mixed with aggregate in a mass ratio of 4:100, and mixed in a mixing pot for 60 seconds to obtain a polyurethane urea mixture after mixing evenly.

[0117] Application Example 2

[0118] The polyurethane urea binder prepared in Example 5 was mixed with aggregate in a mass ratio of 5:100, and mixed in a mixing pot for 60 seconds to obtain a polyurethane urea mixture after mixing evenly.

[0119] Application Example 3

[0120] The polyurethane urea binder prepared in Example 5 was mixed with aggregate in a mass ratio of 6:100, and mixed in a mixing pot for 60 seconds to obtain a polyurethane urea mixture after mixing evenly.

[0121] Application Example 4

[0122] The polyurethane urea binder prepared in Example 5 was mixed with aggregate in a mass ratio of 7:100, and mixed in a mixing pot for 60 seconds to obtain a polyurethane urea mixture after mixing evenly.

[0123] Table 6 shows the road performance test results of the polyurethane urea mixture prepared in Application Examples 1-4, where the high temperature stability is characterized by the dynamic stability measured by the rutting test, the low temperature performance is characterized by the low temperature bending failure strain, the water stability is characterized by the residual stability of the Marshall test, and the anti-skid performance is characterized by the pendulum friction coefficient tester BPN. It can be seen from the table that the road performance of Application Examples 1-4 all meets the requirements of the specification, and the high temperature stability and low temperature performance are greatly improved compared with the specification, indicating that the polyurethane urea mixture has good anti-rutting performance and anti-deformation ability at low temperature.

[0124] Table 6 Road performance test results

[0125]

[0126] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A polyurethane urea binder, characterized in that: The invention comprises the following raw material components in parts by weight: Wherein, the polyurethane component A is a polyurethane having an NCO / OH molar ratio of 1.5-2.5 and a free NCO mass percentage content of 1%-4%; The polyurethane B component is obtained by mixing polyether diol and 1,4-butanediol in a mass ratio of 2:1; The polyurea A component is a polyurea having an NCO mass fraction between 12% and 15%; The polyurea R component is an amino-terminated polyether.

2. The polyurethane urea binder according to claim 1, characterized in that: The chain extender is a diamine.

3. The polyurethane urea binder according to claim 1, characterized in that: The organic solvent is ethyl acetate or butyl acetate.

4. The method for preparing the polyurethane urea binder according to claim 1, characterized in that: The following steps are involved: The raw materials are mixed according to the mass ratio to obtain the polyurethane urea binder.

5. Use of the polyurethane urea binder as claimed in claim 1 as a binder in a polyurethane mixture for pavement.

6. A polyurethane mixture, characterized in that: Contains the polyurethane urea binder according to claim 1.

7. The polyurethane mixture according to claim 6, characterized in that: The polyurethane urea binder described in claim 1 accounts for 4% to 7% of the mass content of the aggregate in the polyurethane mixture.

8. Use of the polyurethane mixture as claimed in any one of claims 6 to 7 as a pavement material.

Citation Information

Patent Citations

  • Polyurethane polyurea modified asphalt mixture as well as preparation and application thereof

    CN106145776A

  • Amino silicon oil modified elastomer material and preparation method thereof

    CN109825180A